2022
DOI: 10.1177/15266028221075548
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Bare Metal Stent Migration Associated With Aortic Remodeling After PETTICOAT Technique for Aortic Dissection

Abstract: Purpose: To report a unique case of bare metal stent migration in the overlapping zone and subsequent distal stent graft-induced new entry (SINE) after the Provisional Extension to Induce a Complete Attachment (PETTICOAT) technique for aortic dissection. Case report: A 67-year-old man underwent thoracic endovascular aortic repair (TEVAR) using the PETTICOAT technique for acute complicated type B aortic dissection. The postoperative course was uneventful, and follow-up computed tomography (CT) showed not only f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…52 Furthermore, there have been occasional reports of complications related to the bare stent, including stent migration, stent fracture, and misalignment. [53][54][55] A Cochrane review of the long-term outcomes of the PETTICOAT was abandoned because the absence of randomized trials precluded definitive assessment of the technique's long-term utility. 56 A meta-analysis by Qui et al that included 914 patients in eight observational studies reported no difference in overall aorta-related mortality or complete false lumen thrombosis in the thoracic or abdominal segments.…”
Section: Petticoatmentioning
confidence: 99%
“…52 Furthermore, there have been occasional reports of complications related to the bare stent, including stent migration, stent fracture, and misalignment. [53][54][55] A Cochrane review of the long-term outcomes of the PETTICOAT was abandoned because the absence of randomized trials precluded definitive assessment of the technique's long-term utility. 56 A meta-analysis by Qui et al that included 914 patients in eight observational studies reported no difference in overall aorta-related mortality or complete false lumen thrombosis in the thoracic or abdominal segments.…”
Section: Petticoatmentioning
confidence: 99%